2012
DOI: 10.1159/000338500
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Reverses Chronic Stress-induced Baroreflex Hypersensitivity in Rats

Abstract: Chronic stress, as a risk factor for cardiovascular diseases, has been reported to result in elevated plasma neuropeptide Y (NPY) and be highly associated with abnormal cardiac autonomic function. This study aimed to explore the effect of NPY on the chronic stress-induced abnormal baroreceptor reflex sensitivity (BRS). Seven types of recognized stressors were used to develop chronic stress rat model. Subcutaneously implanting ALZET mini-osmotic pumps containing NPY were used to evaluate the action of NPY on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…This is an important homeostatic mechanism in the whole body for self-protective functions. Xie et al found that long-term NPY administration induced abnormal baroreflex sensitivity but reversed chronic stressinduced baroreflex hypersensitivity in rats [28,43], providing the evidence of the double controlled role of NPY depending on specific conditions. It's very meaningful to illustrate the effect of NPY on heart function at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important homeostatic mechanism in the whole body for self-protective functions. Xie et al found that long-term NPY administration induced abnormal baroreflex sensitivity but reversed chronic stressinduced baroreflex hypersensitivity in rats [28,43], providing the evidence of the double controlled role of NPY depending on specific conditions. It's very meaningful to illustrate the effect of NPY on heart function at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…A minor pocket was made with a hemostat by spreading the subcutaneous connective tissues apart, the pump was inserted into the pocket while orienting the flow moderator to point to the opposite direction of the incision, and the incision was closed with wound sutures [17,18]…”
Section: Methodsmentioning
confidence: 99%
“…Elevated levels of plasma NPY have also been proposed as a prognostic marker for coronary diseases [13], heart failure [14] and myocardial ischemia [15]. Our previous studies demonstrated that long-term NPY administration led to abnormal BRS, and reversed chronic stress-induced baroreflex hypersensitivity in rats [16,17]. Clinical investigation has shown that the level of plasma NPY is positively correlated with the insulin level for patients with T2DM [18].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that these experimental models of stress may increase the vulnerability and severity of cardiac complications. In addition, cardiac contractile dysfunction was reported in animals subjected to CVS protocols (Grippo et al, 2006 ; Xie et al, 2012 ).…”
Section: Cardiovascular Responses To Stress: Influence Of Chronicitymentioning
confidence: 99%